Strategi Pemanfaatan Media Sosial untuk Meningkatkan Kompetensi Komunikasi Bahasa Inggris Siswa - Kalukar, Ventje Jany; Riasah, Eris Siti; Litta, Lista (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The utilization of social media in education has become a significant innovation in enhancing students’ competencies, particularly in English communication skills. This study aims to analyze strategies for leveraging social media as a learning tool to improve students’ English communication skills. Using a qualitative method with a literature review (library research) approach, this study examines various academic sources, including scholarly journals, books, and reports related to the impact of social media on language learning. The analyzed data focuses on popular social media platforms such as Instagram, YouTube, and TikTok, which hold substantial potential for enhancing students' listening, speaking, reading, and writing skills. The findings reveal that social media can be effectively utilized to create an interactive learning environment that supports English language learning. Strategies such as integrating video-based educational content, conducting online discussions on social media platforms, and developing collaborative online projects help students improve their communication skills in English. Furthermore, social media provides broad access to authentic learning materials, such as videos from native speakers, which enhance students' pronunciation and understanding of natural language contexts. However, challenges such as time management and the potential distractions of social media need to be addressed through structured pedagogical approaches. This study recommends that educators strategically integrate social media into the curriculum and provide clear guidelines for students on how to use social media for learning. With this approach, social media can become an effective tool for improving students' English communication skills in the digital era